Contesting nationalism: the vision of Rabindranath Tagore - Quayum, Mohammad Abdul (2015)
It is universally acknowledged that nationalism is the most deeply ingrained political ideology in the modern imagination. It is as Benedict Anderson suggests, "the most universally legitimate value in the political life of our time." Dipesh Chakrabarty is of the view that European imperialism and Third World nationalism have together achieved the "universalization of the nation-state as the most desirable form of political community." Yet, India's messianic poet and Asia's first Nobel Laureate, Rabindranath Tagore (1861-1941), was fiercely opposed to the ideology of nationalism in all his writings, spruning it as a"cruel epidemic of evil" and a source of "moral cannibalism," that instigated war, violence, oppression, exploitation and national self-aggrandizement. In his poems, lectures, letters, essays, short stories and novels, Tagore again and again roundly condemns the nationalist fervour in both the East and the West and advocates an alternative ideology that would celebrate righteousness and human conscience against the ideology of the nation, and the spirit of inclusivity and togetherness that would bring all the races and communities, as he put it, "in one nest." This paper offers to explore Tagore's anti-nationalitarian outlook in his selected prose and fictional writings, as well as his alternative world view of unity in harmony, worldcentrism, or, what his critics have described as "internationalism (Isaiah Berlin) and "cosmopolitanism" (Martha Nassbaum, Saranindranath Tagore).